Model Agribisnis Impatien Balsamina Sebagai Penggerak Perekonomian Pedesaan dan Pelestarian Budaya Lokal di Bali - Ni Putu Sukanteri; Pande Komang Suparyana; I Ketut Widnyana; I Putu Fajar Kartika Lestari (Jayapangus Press, 2022)
Impatien balsamina flower is one of the agricultural products of rural communities as an agribusiness product that has economic and cultural values. The purpose of this study was to determine the profit, profit sharing and marketing margin of Impatien Balsamina agribusiness, to find out the benefits of Impatien Balsamina flowers in preserving local culture in community activities. daily. The impatient model of balsamina agrbinis research was conducted in Sibang Village, Mengwi District, Badung Regency. This study involved 25 respondents consisting of farmers, marketers and consumers of impatien balsamina flowers. The data analysis method used in this research is the analysis of farmer share and marketing margin of impatien balsamina flower. As well as the economic benefits and its role in preserving local culture which is reflected in everyday life. The results showed that the impatien balsamina flower marketing model involved farmers, village collectors, large collectors, retailers and consumers. The highest profit of agribinis impatiens balsamina interest is obtained by agribinis actors in channel III, namely retailers with an average flower sale of Rp 11,500 per kg. The farmer's share of the research shows that the average share received by the farmer is 120% if the farmer sells it to collectors in the village. And the biggest marketing margin is obtained in marketing channel III. Impatien balsamina flowers as a means of ceremony in the local culture of the Balinese people.